Pemberdayaan Sosial Berbasis Potensi Desa dan Lingkungan Guna Mendorong Kemandirian Masyarakat Desa Pabean Ilir, Indramayu - Tri Amanda Putri Harahap; Adira Nabila; Ilham Bimar; Kamelia Anita Ga’a; Muhammad Derial Poszrevac Saputra; Muhammad Rafi Akbar Askari Putra; Mustika Nurul Hidayati Rahman; Zahara Khairani; Nyoman Metta Nyanakumara Natih (Jurnal Pusat Inovasi Masyarakat, 2026)
Pabean Ilir Village, Pasekan District, Indramayu Regency, faces a number of priority issues including coastal ecosystem degradation due to plastic waste, low utilization of local fish for complementary feeding (MPASI), limited competitiveness of MSME products, weak motivation of the younger generation in achieving their goals, and minimal village spatial data. IPB University's Thematic Community Service Program (KKN-T) is implemented as an effort to empower communities based on village and environmental potential to encourage community independence. This activity aims to increase community capacity in environmental management, health, economy, education, and village planning. The methods used include field observation, interviews, training, demonstrations, participatory actions, and satellite imagery-based spatial mapping. The results of the activities show that the Breath of the Earth program is able to reduce waste accumulation, increase coastal vegetation cover, and increase environmental awareness; the SENYUM program improves mothers' nutritional knowledge and encourages the use of local fish to prevent stunting; the SiPIKIR program strengthens MSME branding and digital marketing; the Mimpi Canvas program fosters motivation, self-confidence, and future orientation of students; and the Mapping program produces maps of village potential, tsunami vulnerability, and fishing areas that strengthen data-based planning. The community's enthusiasm for participating in the program demonstrates the significant potential for sustainable village development. Pabean Ilir Village is expected to become a model for strengthening coastal community independence based on local potential and participatory innovation.